ANALISA TINGKAT KETAHANAN TERHADAP KEBAKARAN DI KAWASAN PESISIR KOTA TARAKAN - Setiawan, Budi (Jurnal Harpodon Borneo, 2016)
Settlements in coastal areas near urban areas is generally a densely populated residential and buildings. This condition can cause social disasters such as fire. The fire is likely to occur due to a lack of knowledge and awareness of inhabitants of coastal areas against, the risk of fire and lack of prevention and fire-fighting facilities. This study reviews the level of capacity to fire in the residential area of the coastal area in Tarakan city with variable capacity fire department of the city, availability of hydrant or water resources, human resources, facilities and infrastructure fire prevention, public awareness and information as well as sets of laws. Analysis of the level capacity to fire is done by collecting data from survey then the data is transformed into a value weighting scale capacity. Then use expert opinion in the field of fire prevention to assess the value of a variable with AHP method. Furthermore, the classification level of capacity to fire in the coastal area with equal interval method of mapping class and level of capacity to fire. The research location is a residential area of coastal town of Tarakan which includes: Lingkas Ujung Village, Mamburungan Village, Pantai Amal Village, Selumit Pantai Village, Karang Rejo village, Karang Anyar village, and Juata Laut Village. From the analysis, the level of capacity to fire in the coastal area of TarakanCity indicated by the classification is very high, high, medium and low classification. Keywords: capacity, fires, coastal areas